What Determines Foreign Direct Investment in Indonesia? - Euis Eti Sumiyati (Journal of Economics, Business, and Accountancy Ventura, 2021)
This study aims to determine the determinants of foreign direct investment (FDI) in Indonesia's manufacturing sector. This study uses time-series data with 40 data observations starting from the 1st quarter of 2010 to the 4th quarter of 2020. The data analysis method employed in this research was Autoregressive Distributed Lag (ARDL) cointegration approach. The research results were that in the long run, the exchange rate and GDP growth had a positive effect, inflation had a negative effect, and gross fixed capital formation did not affect the FDI inflows in the manufacturing sector. This research implies that the government must be able to create or develop policies related to foreign direct investment to provide benefits for economic development in Indonesia. The government's efforts to control inflation have to be strengthened continuously by maintaining the availability of supply and distribution of goods. Supply continuity and smooth distribution between regions have to be further improved through the utilization of information technology and the strengthening of inter-regional cooperation. Likewise, efforts to increase economic growth have to continue to be improved by providing incentives or facilities to companies at various levels, both those that are export-oriented and those that focus on domestic sales.Â Â